2018
DOI: 10.1002/jbt.22244
|View full text |Cite
|
Sign up to set email alerts
|

Bldesin, the first functionally characterized pathogenic fungus defensin with Kv1.3 channel and chymotrypsin inhibitory activities

Abstract: Fungus defensin is a kind of important natural peptide resource, such as plectasin from the soil fungus Pseudoplectania nigrella with potential application in the antimicrobial peptide lead drug discovery. Here, a fungus defensin named Bldesin with Kv1.3 channel and serine protease inhibitory activities was first explored. By GST-Bldesin fusion expression and enterokinase cleaving strategy, recombinant Bldesin was obtained successfully. Antimicrobial assays showed that Bldesin had potent activity against Gramp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…For example, metabolites or small molecules from fungus, Aspergillus fumigatus has anti-cancer potential; these small molecules are responsible for pathogenicity as well as the virulence nature of the fungus, A. fumugatus [ 16 ]. Previous reports [ 17 , 18 ] indicate that pathogenic fungus-derived virulence factors and the venom of numerous species including bees, snakes, scorpions and plant-derived toxins have significant anti-cancer activities. In line with this context, we hypothesized that the CBD protein-derived PS14 peptide could have significant anti-cancer potential.…”
Section: Resultsmentioning
confidence: 99%
“…For example, metabolites or small molecules from fungus, Aspergillus fumigatus has anti-cancer potential; these small molecules are responsible for pathogenicity as well as the virulence nature of the fungus, A. fumugatus [ 16 ]. Previous reports [ 17 , 18 ] indicate that pathogenic fungus-derived virulence factors and the venom of numerous species including bees, snakes, scorpions and plant-derived toxins have significant anti-cancer activities. In line with this context, we hypothesized that the CBD protein-derived PS14 peptide could have significant anti-cancer potential.…”
Section: Resultsmentioning
confidence: 99%
“…Remarkably, a potassium channel inhibitory activity could be revealed for the N-terminal one, Purlisin-NT. Fungal defensins targeting voltage gated Kv1.3 channels have been described before (Xiang et al, 2015;Luo et al, 2019), and considering the high degree of conservation between Purlisin-NT and AfusinN, the latter might be one of those as well. Such channels are expressed in numerous human cells, among them macrophages and T lymphocytes in which they are involved in cell proliferation and activation as well as cytokine production (reviewed by Feske et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A small number of fungal-derived defensins, such as plectasin and bldesin, possessed dual or multiple biological effects. 6,45,46 But unlike them, purlisin achieved different functions by dividing itself into two separate molecules. The purlisin-NT has a strong inhibitory effect on hKv1.3 potassium channel like animal-toxin and extremely weak antibacterial activity.…”
Section: Discussionmentioning
confidence: 99%
“…The biological effect studies have revealed that purlisin was a bifunctional molecule coupled with antimicrobial and potassium channel blocking activities. A small number of fungal‐derived defensins, such as plectasin and bldesin, possessed dual or multiple biological effects 6,45,46 . But unlike them, purlisin achieved different functions by dividing itself into two separate molecules.…”
Section: Discussionmentioning
confidence: 99%